The Influence of Perceived Organizational Support on Employee Well-Being: The Mediating Roles of Work-Life Balance and Emotional Exhaustion among Correctional Officers - Sari, Niken Desvita; Martdianty, Fanny (Ilomata International Journal of Management, 2026)
Correctional officers are required to work in an environment that is often characterized by high pressure and demanding situations, making psychological and emotional support in the workplace increasingly important. Recognizing this, this study aims to analyze the influence of perceived organizational support on employee well-being, focusing on the mediating role of work-life balance and emotional exhaustion. This study used a quantitative approach involving 314 correctional officers working in prisons, LPKAs, and detention centers under the authority of the DKI Jakarta Regional Office of the Ministry of Immigration and Corrections. Data was collected through the distribution of questionnaires, with the application of various analytical techniques, including feasibility tests, pilot tests, validity and reliability assessments, descriptive analysis, and measurement and structural model analysis. The results showed that perceived organizational support has a positive and significant effect on employee well-being, both directly and through the mediation of work-life balance and emotional exhaustion. Work-life balance proved to be a mediator that strengthens the relationship, where the higher the organizational support, the better work-life balance employees perceive. In contrast, emotional exhaustion acts as a negative mediator, where strong organizational support is able to reduce the level of emotional exhaustion, thus improving well-being. In conclusion, organizational support plays a crucial role in creating psychologically healthy working conditions, strengthening life balance, and reducing employees' emotional burden. The findings provide practical implications for human resource management in correctional settings to focus more on creating a supportive and well-being-oriented work climate for employees.